2020
DOI: 10.11591/ijphs.v9i3.20434
|View full text |Cite
|
Sign up to set email alerts
|

Complementary treatment to reduce blood sugar levels of type 2 diabetes mellitus patients

Abstract: Diabetes mellitus is a chronic disease that requires long-term management. There is a tendency in type 2 diabetes mellitus patients to use herbs as a complement to medical treatment. The purpose of this study was to analyze the use of herbs as a complement to medical treatment in reducing blood sugar levels of T2DM patients. This type of research is quasi-experimental, with 40 research subjects divided into 4 groups. Determination of research subjects by purposive sampling in accordance with established inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
3
Order By: Relevance
“…One study showed that women who drank at least one or more sugar-sweetened beverages were at risk for T2DM compared to those who drank less frequently with mediated weight gain. Proboningsih et al [31] found that bitter melon can be used as a medical treatment for reducing blood sugar levels. However, it will work when it is balanced with self-care regularly.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that women who drank at least one or more sugar-sweetened beverages were at risk for T2DM compared to those who drank less frequently with mediated weight gain. Proboningsih et al [31] found that bitter melon can be used as a medical treatment for reducing blood sugar levels. However, it will work when it is balanced with self-care regularly.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with T2DM as sufferers of chronic diseases tend to use herbs to manage their illness [25] [26]. Perceived selfefficacy is a strong predictor associated with the use of herbs as a complement to diabetes self-care in regulating blood glucose levels [25].…”
Section: Change Of Medication Patternmentioning
confidence: 99%
“…Asosiasi ini dilemahkan tetapi tetap signifikan setelah disesuaikan dengan BMI. Konsisten dengan analisis kami sebelumnya, konsumsi kacang tanah dan kacang pohon secara teratur juga dikaitkan dengan risiko diabetes tipe 2 yang lebih rendah secara signifikan, tetapi hubungan ini sebagian besar dijelaskan oleh berat badan (Pan, Sun, Manson, Willett, & Hu, 2013) (Javad et al, 2016).…”
Section: Pembahasanunclassified
“…Pengaruh konsumsi harian asam alfa-lipoat, sebagai antioksidan, selama dua bulan dibandingkan plasebo pada pasien DM tipe 2. Diamati bahwa pada kelompok yang menerima asam alfa-lipoat, FBS dan permintaan model homeostasis resistensi insulin (IR-HOMA) menurun secara signifikan tetapi berat badan tetap tidak berubah (Javad et al, 2016).…”
Section: Pembahasanunclassified
See 1 more Smart Citation